toner
Patent Information
- Application Number
- JP2021128067
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2021-08-04
- Publication Date
- 2025-03-27
- Estimated Expiration
- 2041-08-04
AI Technical Summary
【0008】 本発明のトナーは、画像濃度安定性、帯電安定性及び耐フィルミング性に優れる。
Smart Images

Figure 0007652007000007 
Figure 0007652007000008 
Figure 0007652007000009
Abstract
Description
[Technical field]
[0001] The present invention relates to a toner. [Background technology]
[0002] In image formation by electrophotography, for example, a non-magnetic one-component developer is used. The non-magnetic one-component developer has a toner containing toner particles. The toner is required to have excellent performance in stably continuing to form an image with a desired image density (image density stability) and excellent charging stability. In addition, in image formation by electrophotography, an image defect called filming may occur due to the toner components adhering to the surface of the photoconductor drum. Therefore, the toner is required to have excellent performance in suppressing the occurrence of filming (filming resistance).
[0003] As a toner having excellent image density stability and charge stability, for example, a toner containing fluororesin particles has been studied. Fluororesin particles have low surface adhesion. Therefore, a toner containing fluororesin particles tends to have excellent fluidity and charge stability. As a toner using fluororesin particles, for example, a toner containing toner particles containing a binder resin and a colorant, polytetrafluoroethylene particles attached to the surface of the toner particles, and monodisperse spherical silica particles has been proposed (Patent Document 1). [Prior art documents] [Patent documents]
[0004] [Patent Document 1] JP 2010-197732 A Summary of the Invention [Problem to be solved by the invention]
[0005] However, even the toner described in Patent Document 1 does not necessarily satisfy all of the image density stability, charge stability, and filming resistance.
[0006] The present invention has been made in view of the above problems, and an object of the present invention is to provide a toner having excellent image density stability, charge stability and filming resistance. [Means for solving the problem]
[0007] The toner of the present invention includes toner particles. The toner particles include toner base particles and an external additive attached to the surface of the toner base particles. The external additive includes first external additive particles and fluorine-containing particles. The first external additive particles include aluminum oxide particles, a conductive layer covering the aluminum oxide particles, and a single-layer or multi-layer protective layer covering the conductive layer. The conductive layer contains antimony-doped tin oxide. The protective layer has a layer containing a component derived from a titanate coupling agent, or has an inner layer containing methylol melamine, a urethane resin, or aluminum hydroxide, and an outer layer containing a component derived from a silane coupling agent. The powder resistivity of the first external additive particles is 50 Ω·cm or less. The number-average primary particle diameter of the first external additive particles is 60 nm or more and 600 nm or less. Effect of the Invention
[0008] The toner of the present invention is excellent in image density stability, charge stability and filming resistance. [Brief description of the drawings]
[0009] [Figure 1] FIG. 2 is a diagram showing an example of a toner particle contained in the toner of the present invention. [Diagram 2] FIG. 2 is a diagram showing an example of a first external additive particle. [Diagram 3] 3 is a diagram showing another example of the first external additive particle different from that shown in FIG. 2. FIG. [Figure 4] FIG. 2 is a diagram showing an example of a fluorine-containing particle. [Diagram 5] FIG. 5 is a diagram showing another example of a fluorine-containing particle different from that shown in FIG. [Figure 6] FIG. 4 is a diagram showing an evaluation image formed in the evaluation of toner collectability in the examples. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0010] A preferred embodiment of the present invention will be described below. The toner is an aggregate (e.g., powder) of toner particles. The external additive is an aggregate (e.g., powder) of external additive particles. Unless otherwise specified, the evaluation results (values indicating shape, physical properties, etc.) of the powder (more specifically, the powder of toner particles, the powder of external additive particles, etc.) are the number averages of values measured for each of a considerable number of particles selected from the powder.
[0011] Volume median diameter of powder (D 50 ) unless otherwise specified, the measured value is a value measured based on the Coulter principle (pore electrical resistance method) using a Coulter Counter Multisizer 3 manufactured by Beckman Coulter, Inc.
[0012] Unless otherwise specified, the number average primary particle diameter of a powder is the number average value of the circle equivalent diameters of primary particles (Heywood diameter: diameter of a circle having the same area as the projected area of a primary particle) measured using a scanning electron microscope. The number average primary particle diameter of a powder is, for example, the number average value of the circle equivalent diameters of 100 primary particles. Note that the number average primary particle diameter of particles refers to the number average primary particle diameter of particles in a powder unless otherwise specified.
[0013] Unless otherwise specified, the term "chargeability" refers to the chargeability in triboelectric charging. The strength of positive chargeability (or negative chargeability) in triboelectric charging can be confirmed by a known triboelectric series. For example, the toner is mixed with a standard carrier provided by the Imaging Society of Japan (standard carrier for negatively charged toner: N-01, standard carrier for positively charged toner: P-01) and stirred to triboelectrically charge the measurement object. The charge amount of the measurement object is measured before and after triboelectric charging, for example, with a charge amount measuring device (Q / m meter), and the larger the change in charge amount before and after triboelectric charging, the stronger the chargeability of the measurement object.
[0014] Unless otherwise specified, the "major component" of a material means the component that is contained in the largest amount in the material on a mass basis.
[0015] The strength of hydrophobicity (or strength of hydrophilicity) can be expressed, for example, by the contact angle of a water droplet (ease of wetting with water). The larger the contact angle of the water droplet, the stronger the hydrophobicity.
[0016] Hereinafter, the compound and its derivatives may be collectively referred to by adding "based" after the compound name. When the compound name is followed by "based" to represent the name of a polymer, it means that the repeating unit of the polymer is derived from the compound or its derivative.
[0017] <Toner> The toner according to the embodiment of the present invention includes toner particles. The toner particles include toner base particles and an external additive attached to the surface of the toner base particles. The external additive includes first external additive particles and fluorine-containing particles. The first external additive particles include aluminum oxide particles, a conductive layer covering the aluminum oxide particles, and a single-layer or multi-layer protective layer covering the conductive layer. The conductive layer contains antimony-doped tin oxide. The protective layer has a layer containing a component derived from a titanate coupling agent, or has an inner layer containing methylol melamine, urethane resin, or aluminum hydroxide, and an outer layer containing a component derived from a silane coupling agent. The powder resistivity of the first external additive particles is 50 Ω·cm or less. The number-average primary particle diameter of the first external additive particles is 60 nm or more and 600 nm or less.
[0018] The toner of the present invention can be suitably used, for example, as a positively charged toner for developing an electrostatic latent image. The toner can be used as a one-component developer. When used as a one-component developer, the toner is, for example, positively charged by friction with a developer carrier or a toner charging member in a developing device. An example of the toner charging member is a developer regulating blade. The toner will be described in detail below with reference to the drawings as appropriate.
[0019] The toner of the present invention has excellent image density stability, charge stability, and filming resistance due to the above-mentioned configuration. The reason is explained below. The toner of the present invention contains fluorine-containing particles, which are particles with low surface adhesion, as an external additive, and therefore has excellent fluidity. Therefore, the toner of the present invention can be stably charged in the developing device. On the other hand, when continuous printing is performed with a toner containing fluorine-containing particles, the potential difference between the developer carrier and the toner charging member and the toner may become excessively large. In detail, when continuous printing is performed using a toner containing fluorine-containing particles, a part of the fluorine-containing particles is detached from the toner and adheres to the developer carrier and the toner charging member in the developing device. Since the fluorine-containing particles have negative charging properties, the developer carrier and the toner charging member to which the fluorine-containing particles are attached are negatively charged. As a result, the potential difference between the developer carrier and the toner charging member and the toner becomes excessively large. As a result, the amount of toner transported by the developer carrier gradually increases during continuous printing, and the image density of the formed image gradually increases.
[0020] In contrast, the toner of the present invention contains first external additive particles in addition to fluorine-containing particles as an external additive. The first external additive particles have a conductive layer containing antimony-doped tin oxide (ATO), and therefore have excellent conductivity (powder resistivity of 50 Ω·cm or less). By containing the first external additive particles, the toner of the present invention can suppress the potential difference between the developer carrier and the toner charging member and the toner from becoming excessively large even when the developer carrier and the toner charging member are negatively charged. As a result, the toner of the present invention can maintain the image density of the formed image constant even when continuously printed. In addition, the protective layer of the first external additive particles is highly hydrophobic and has excellent strength. As a result, the first external additive particles can exert the above-mentioned effects over a long period of time. Therefore, the toner of the present invention has excellent image density stability. Furthermore, the aluminum oxide particles have a relatively high hardness and excellent abrasive action. The toner of the present invention can efficiently clean the surface of the photoconductor drum by containing the first external additive particles having aluminum oxide particles as a base. As a result, the toner of the present invention can clean the toner components adhering to the surface of the photoconductor drum, and therefore has excellent filming resistance. Furthermore, since the first external additive particles have an appropriate number average primary particle diameter, the above-mentioned effects can be stably exhibited.
[0021] The toner of the present invention will be described in further detail below. Each of the components described below may be used alone or in combination of two or more, unless otherwise specified.
[0022] [Toner particles] Fig. 1 shows an example of a toner particle 1 contained in a toner. The toner particle 1 shown in Fig. 1 includes a toner base particle 2 and an external additive 3 attached to the surface of the toner base particle 2. The external additive 3 includes first external additive particles 3a, fluorine-containing particles 3b, and silica particles 3c.
[0023] However, the toner particles contained in the toner of the present invention may have a structure different from that of the toner particle 1 shown in FIG. 1. Specifically, the toner particles may contain at least the first external additive particles and the fluorine-containing particles as external additives. The toner particles may further contain external additive particles other than the first external additive particles, the fluorine-containing particles, and the silica particles (hereinafter, sometimes referred to as other external additive particles) as external additives. Furthermore, the toner particles may be toner particles having a shell layer (hereinafter, sometimes referred to as capsule toner particles). In the capsule toner particles, the toner mother particles have, for example, a toner core containing a binder resin and a shell layer covering the surface of the toner core. The details of the toner particles contained in the toner of the present invention have been described above based on FIG. 1.
[0024] [First external additive particle] Fig. 2 shows an example of a first external additive particle 3a. The first external additive particle 3a shown in Fig. 2 includes an aluminum oxide particle 4, a conductive layer 5 that covers the aluminum oxide particle 4, and a multilayer protective layer 6 that covers the conductive layer 5. The multilayer protective layer 6 includes an inner layer 6a that directly covers the conductive layer 5, and an outer layer 6b that covers the inner layer 6a.
[0025] Fig. 3 shows another example of the first external additive particle 3a different from that shown in Fig. 2. The first external additive particle 3a shown in Fig. 3 includes an aluminum oxide particle 4, a conductive layer 5 covering the aluminum oxide particle 4, and a single-layer protective layer 7 covering the conductive layer 5. The first external additive particle 3a shown in Fig. 3 differs from the first external additive particle 3a shown in Fig. 2 in that it includes a single-layer protective layer 7 instead of the multi-layer protective layer 6.
[0026] Above, examples of the first external additive particles have been described with reference to Figs. 2 and 3. However, the structure of the first external additive particles is not limited to Figs. 2 and 3. Specifically, the first external additive particles may further include other layers in addition to the conductive layer and the protective layer. The conductive layer is preferably a single layer, but may be multilayered. The protective layer is preferably a single layer or two layers, but may be three or more layers. The details of the first external additive particles will be further described below.
[0027] The powder resistivity of the first external additive particles is 50 Ω·cm or less, and preferably 30 Ω·cm or less. By setting the powder resistivity of the first external additive particles to 50 Ω·cm or less, the toner of the present invention has excellent image density stability. The powder resistivity of the first external additive particles is measured by the method described in the Examples or a method based thereon.
[0028] The number average primary particle diameter of the first external additive particles is preferably 60 nm to 600 nm, more preferably 150 nm to 250 nm. By setting the number average primary particle diameter of the first external additive particles to 60 nm or more, it is possible to prevent the first external additive particles from being embedded in the toner base particles. By setting the number average primary particle diameter of the first external additive particles to 600 nm or less, it is possible to prevent the first external additive particles from being detached from the toner base particles.
[0029] The content of the first external additive particles in the toner particles is preferably 0.1 parts by weight or more and 5.0 parts by weight or less, and more preferably 0.3 parts by weight or more and 2.0 parts by weight or less, relative to 100 parts by weight of the toner base particles, from the viewpoint of fully exerting its function while suppressing detachment from the toner base particles.
[0030] (Aluminum oxide particles) The aluminum oxide particles are the substrate of the first external additive particles. The aluminum oxide particles are aluminum oxide (specifically, Al 2 O 3 The content of aluminum oxide in the aluminum oxide particles is preferably 80% by mass or more, more preferably 95% by mass or more, and even more preferably 100% by mass.
[0031] The aluminum oxide particles can be obtained, for example, by calcining aluminum hydroxide and then pulverizing the calcined aluminum hydroxide using a pulverizer.
[0032] (Conductive layer) The conductive layer contains antimony-doped tin oxide (ATO). The content of ATO in the conductive layer is preferably 80% by mass or more, more preferably 95% by mass or more, and even more preferably 100% by mass.
[0033] A method for coating aluminum oxide particles with a conductive layer containing antimony-doped tin oxide is described below. First, aluminum oxide particles are dispersed in an aqueous solvent (e.g., water). Next, stannic chloride (SnCl 4 ) and antimony trichloride (SbCl 3 ) dissolved in hydrochloric acid, and an alkaline aqueous solution (e.g., an ammonia aqueous solution) are added. As a result, a coating layer is formed on the surface of the aluminum oxide particles. The aluminum oxide particles on which the coating layer is formed are then fired (e.g., heating temperature of 600°C to 800°C, heating time of 1 hour to 4 hours), thereby obtaining aluminum oxide particles coated with a conductive layer containing antimony-doped tin oxide. When the above-mentioned acid aqueous solution and alkaline aqueous solution are added, it is advisable to maintain the pH and temperature of the suspension within a certain range (e.g., pH 6.5 to 9.0, and 60°C to 80°C).
[0034] (protective layer) The protective layer suppresses peeling of the conductive layer. The protective layer has a single layer structure or a multilayer structure (for example, a two-layer structure). Specifically, the protective layer has a layer containing a component derived from a titanate coupling agent, or has an inner layer containing methylol melamine, a urethane resin, or aluminum hydroxide, and an outer layer containing a component derived from a silane coupling agent. Since the protective layer has the above-mentioned layer structure, it has high hydrophobicity and excellent strength. In detail, the layer containing a component derived from a titanate coupling agent has high hydrophobicity and excellent strength, and therefore functions as a protective layer by itself. The inner layer containing methylol melamine, a urethane resin, or aluminum hydroxide has excellent strength. The outer layer containing a component derived from a silane coupling agent has high hydrophobicity. Therefore, by combining the above-mentioned inner layer and outer layer, it functions as a protective layer.
[0035] In addition to the above-mentioned layers, the protective layer may further have other layers.The other layers may include, for example, a layer containing silicone oil.The layer containing silicone oil is suitable as an outer layer because it has high hydrophobicity, similar to the outer layer containing the component derived from silane coupling agent.
[0036] (Titanate coupling agent) Examples of titanate coupling agents include isopropyl triisostearoyl titanate, isopropyl tris(dioctyl pyrophosphate) titanate, isopropyl tri(N-aminoethyl-aminoethyl) titanate, tetraoctyl bis(ditridecyl phosphite) titanate, isopropyl trioctanoyl titanate, isopropyl dimethacryl isostearoyl titanate, isopropyl tridodecyl benzene sulfonyl titanate, isopropyl isostearoyl diacryl titanate, or isopropyl tri(dioctyl phosphate) titanate.As the titanate coupling agent, isopropyl triisostearoyl titanate is preferred.
[0037] (Silane coupling agent) The silane coupling agent includes alkylalkoxysilanes, and the alkyl group contained in the alkylalkoxysilanes is preferably an alkyl group having 3 to 8 carbon atoms.
[0038] Examples of alkylalkoxysilanes include propyltrimethoxysilane (more specifically, n-propyltrimethoxysilane, isopropyltrimethoxysilane, etc.), propyltriethoxysilane (more specifically, n-propyltriethoxysilane, isopropyltriethoxysilane, etc.), butyltrimethoxysilane (more specifically, n-butyltrimethoxysilane, isobutyltrimethoxysilane, etc.), butyltriethoxysilane (more specifically, n-butyltriethoxysilane, isobutyltriethoxysilane, etc.), hexyltrimethoxysilane (more specifically, n-hexyltrimethoxysilane, etc.), hexyltriethoxysilane (more specifically, n-hexyltriethoxysilane, etc.), octyltrimethoxysilane (more specifically, n-octyltrimethoxysilane, etc.), and octyltriethoxysilane (more specifically, n-octyltriethoxysilane, etc.).
[0039] As the silane coupling agent, alkylalkoxysilane is preferred, monoalkyltrialkoxysilane is more preferred, and isobutyltriethoxysilane is even more preferred.
[0040] (Silicone oil) Examples of silicone oils include straight silicone oils (more specifically, dimethyl silicone oil, methylphenyl silicone oil, and methylhydrogen silicone oil, etc.), reactive modified silicone oils (more specifically, amino modified silicone oil, epoxy modified silicone oil, carboxyl modified silicone oil, mercapto modified silicone oil, methacrylic acid modified silicone oil, phenol modified silicone oil, and alcohol modified silicone oil, etc.), and non-reactive modified silicone oils (more specifically, alkyl modified silicone oil, higher fatty acid modified silicone oil, fluorine modified silicone oil, polyether modified silicone oil, and methylstyryl modified silicone oil, etc.).As silicone oils, straight silicone oils are preferred, and methylhydrogen silicone oils are more preferred.
[0041] Methods for forming the protective layer include, for example, a method in which the raw material components of the protective layer are dropped or sprayed into a solution containing aluminum oxide particles coated with a conductive layer while stirring the solution, and then heated; and a method in which aluminum oxide particles coated with a conductive layer are added to a solution of the raw material components of the protective layer while stirring the solution, and then heated.
[0042] The raw material components of the protective layer include a combination of polyaluminum chloride and a basic solution (e.g., aqueous sodium hydroxide solution), a titanate coupling agent, a melamine resin, a urethane resin, a silane coupling agent, and a silicone oil. When a combination of polyaluminum chloride and a basic solution is used as the raw material components of the protective layer, a protective layer containing aluminum hydroxide is formed.
[0043] The layer structure of the protective layer in the first external additive particle is preferably any of the following (A) to (C). (A) A single layer structure including a layer containing a component derived from a titanate coupling agent. (B) A two-layer structure including an inner layer containing a component derived from a titanate coupling agent and an outer layer containing a component derived from a silane coupling agent or a silicone oil. (C) A two-layer structure including an inner layer containing methylol melamine, a urethane resin or aluminum hydroxide and an outer layer containing a component derived from a silane coupling agent.
[0044] The first external additive particles can be prepared by coating aluminum oxide particles with a conductive layer and a protective layer in that order by the above-mentioned method.
[0045] [Fluorine-containing particles] The fluorine-containing particles are particles that contain a fluorine component, such as a fluorine resin, a component derived from a fluorine-containing silane coupling agent, or a fluorine-modified silicone oil.
[0046] The fluorine-containing particles are preferably fluororesin particles or second external additive particles. The second external additive particles include a substrate and a fluorine component layer that covers the substrate. The fluorine component layer contains a component derived from a fluorine-containing silane coupling agent or a fluorine-modified silicone oil.
[0047] Fig. 4 shows an example of a fluorine-containing particle 3b. The fluorine-containing particle 3b shown in Fig. 4 is a fluororesin particle 8. Fig. 5 shows another example of the fluorine-containing particle 3b different from that shown in Fig. 4. The fluorine-containing particle 3b shown in Fig. 5 is a second external additive particle including a base 9 and a fluorine component layer 10 coating the base 9.
[0048] Above, examples of fluorine-containing particles have been described with reference to the drawings. However, the structure of the fluorine-containing particles is not limited to FIG. 4 and FIG. 5. Specifically, the second external additive particles may further have layers other than the fluorine component layer. In addition, the fluorine component layer is preferably a single layer, but may be a multilayer. Hereinafter, the details of the fluorine-containing particles will be further described.
[0049] (Fluororesin particles) The fluororesin particles contain a fluororesin. The content of the fluororesin in the fluororesin particles is preferably 80% by mass or more, more preferably 95% by mass or more, and even more preferably 100% by mass.
[0050] Examples of the fluororesin include polytetrafluoroethylene (PTFE), perfluoroalkoxy fluororesin, polychlorotrifluoroethylene, polyvinylidene fluoride, polydichlorodifluoroethylene, tetrafluoroethylene n-perfluoroalkyl vinyl ether copolymer, tetrafluoroethylene-hexafluoropropylene copolymer, tetrafluoroethylene-ethylene copolymer, tetrafluoroethylene-hexafluoropropylene-perfluoroalkyl vinyl ether copolymer, and tetrafluoroethylene-perfluoroalkoxy ethylene copolymer. The fluororesin is preferably polytetrafluoroethylene or perfluoroalkoxy fluororesin.
[0051] (Second external additive particles) The second external additive particle includes a substrate and a fluorine component layer covering the substrate. The fluorine component layer contains a component derived from a fluorine-containing silane coupling agent or a fluorine-modified silicone oil.
[0052] In the second external additive particles, the mass of the fluorine component layer relative to 100 parts by mass of the base is preferably from 1 part by mass to 40 parts by mass, and more preferably from 5 parts by mass to 20 parts by mass.
[0053] Methods for forming a fluorine component layer include, for example, a method in which the raw material components of the fluorine component layer are dropped or sprayed into a solution containing the substrate while stirring the solution, and then heated; and a method in which the substrate is added to a solution of the raw material components of the fluorine component layer while stirring the solution, and then heated.
[0054] (Base) Examples of the substrate of the second external additive particles include silica particles, metal oxide particles (for example, aluminum oxide particles and titanium oxide particles), and resin particles. As the substrate of the second external additive particles, silica particles are preferred.
[0055] (Fluorine-containing silane coupling agent) Examples of fluorine-containing silane coupling agents include CF 3 (CH 2 ) 2 Si(OCH 3 ) 3 , C 4 F 9 CH 2 CH 2 Si(OCH 3 ) 3 , C 8 F 17 CH 2 CH 2 Si(OCH 3 ) 3 , C 7 F 15 COOCH 2 CH 2 CH 2 Si(OCH 3 )3 、C 7 F 15 COSCH 2 CH 2 CH 2 They (AND) 3 ) 3 、C 7 F 15 CONHCH 2 CH 2 CH 2 Si(OC 2 H 5 ) 3 、C 7 F 15 CONHCH 2 CH 2 CH 2 They (AND) 3 ) 3 、C 8 F 17 SO 2 NHCH 2 CH 2 CH 2 Si(OC 2 H 5 ) 3 、C 8 F 17 CH 2 CH 2 SCH 2 CH 2 They (AND) 3 ) 3 、C 10 F 21 CH 2 CH 2 SCH 2 CH 2 They (AND) 3 ) 3 、C 8 F 17 CH 2 CH 2 SiCH 3 (AS WELL 3 ) 2 、C 8 F 17 SO 2 N(CH 2 CH 2 CH 3 )CH 2 CH 2 CH 2 They (AND) 3) 3 , and C 8 F 17 SO 2 NHCH 2 CH 2 N(SO 2 C 8 F 17 )CH 2 CH 2 CH 2 Si(OCH 3 ) 3 Examples of fluorine-containing silane coupling agents include CF 3 (CH 2 ) 2 Si(OCH 3 ) 3 is preferred.
[0056] (Fluorine modified silicone oil) An example of the fluorine-modified silicone oil is a silicone oil having a fluoroalkyl group (for example, "FL-100" manufactured by Shin-Etsu Chemical Co., Ltd.).
[0057] The number-average primary particle diameter of the fluorine-containing particles is preferably 50 nm or more and 300 nm or less, more preferably 75 nm or more and 150 nm or less. By making the number-average primary particle diameter of the fluorine-containing particles 50 nm or more, it is possible to prevent the fluorine-containing particles from being embedded in the toner base particles. By making the number-average primary particle diameter of the fluorine-containing particles 300 nm or less, it is possible to prevent the fluorine-containing particles from being detached from the toner base particles.
[0058] The content of the fluorine-containing particles in the toner particles is preferably from 0.05 parts by mass to 3.0 parts by mass, and more preferably from 0.1 parts by mass to 1.0 parts by mass, per 100 parts by mass of the toner base particles, from the viewpoint of suppressing detachment from the toner base particles while fully exerting their function.
[0059] [Silica particles] The silica particles used as the external additive particles are preferably silica particles that have been subjected to a surface treatment to impart positive charging properties. The number-average primary particle diameter of the silica particles is preferably 10 nm or more and 300 nm or less, more preferably 15 nm or more and 80 nm or less. By making the number-average primary particle diameter of the silica particles 10 nm or more, it is possible to suppress embedding of the silica particles in the toner base particles. By making the number-average primary particle diameter of the silica particles 300 nm or less, it is possible to suppress detachment from the toner base particles.
[0060] From the viewpoint of fully exerting the function of the silica particles while suppressing detachment from the toner base particles, the content of the silica particles in the toner particles is preferably 0.1 parts by mass or more and 15.0 parts by mass or less, and more preferably 0.5 parts by mass or more and 3.0 parts by mass or less, per 100 parts by mass of the toner base particles.
[0061] (Other external additive particles) Other external additive particles include, for example, particles of metal oxides (specifically, aluminum oxide, magnesium oxide, zinc oxide, etc.), particles of organic acid compounds such as fatty acid metal salts (specifically, zinc stearate, etc.), and resin particles.
[0062] [Toner base particles] The toner base particles are not particularly limited, and toner base particles in known toners can be used. The toner base particles contain, for example, a binder resin as a main component. The toner base particles may further contain an internal additive (for example, at least one of a colorant, a release agent, and a charge control agent) as necessary. Methods for producing the toner base particles include a pulverization method and an aggregation method, and the pulverization method is preferred.
[0063] From the viewpoint of forming a good image, the volume median diameter (D 50 ) is preferably 4 μm or more and 9 μm or less.
[0064] (Binding resin) From the viewpoint of providing a toner having excellent low-temperature fixing properties, the toner base particles preferably contain a thermoplastic resin as a binder resin, and more preferably contain a thermoplastic resin in a proportion of 85% by mass or more of the total binder resin. Examples of the thermoplastic resin include styrene resins, acrylic ester resins, olefin resins (more specifically, polyethylene resins, polypropylene resins, etc.), vinyl resins (more specifically, vinyl chloride resins, polyvinyl alcohol, vinyl ether resins, N-vinyl resins, etc.), polyester resins, polyamide resins, and urethane resins. In addition, copolymers of these resins, that is, copolymers in which any repeating unit is introduced into the above resins (more specifically, styrene-acrylic ester resins, styrene-butadiene resins, etc.), can also be used as the binder resin. As the binder resin, polyester resins are preferred.
[0065] The content of the binder resin in the toner base particles is preferably from 60% by mass to 95% by mass, and more preferably from 75% by mass to 90% by mass.
[0066] (Coloring agent) The toner base particles may contain a colorant. As the colorant, a known pigment or dye can be used according to the color of the toner. From the viewpoint of forming a high-quality image using the toner, the content of the colorant is preferably 1 part by mass or more and 20 parts by mass or less with respect to 100 parts by mass of the binder resin.
[0067] The toner base particles may contain a black colorant. An example of the black colorant is carbon black. The black colorant may be a colorant toned to black using a yellow colorant, a magenta colorant, and a cyan colorant.
[0068] The toner base particles may contain color colorants, including yellow, magenta, and cyan colorants.
[0069] (Release agent) The toner base particles may contain a release agent. The release agent is used, for example, for the purpose of imparting offset resistance to the toner. From the viewpoint of imparting sufficient offset resistance to the toner, the content of the release agent is preferably 1 part by mass or more and 20 parts by mass or less with respect to 100 parts by mass of the binder resin.
[0070] Examples of the release agent include aliphatic hydrocarbon waxes, oxides of aliphatic hydrocarbon waxes, vegetable waxes, animal waxes, mineral waxes, ester waxes mainly composed of fatty acid esters, and waxes in which a part or all of the fatty acid esters are deoxidized. Examples of the aliphatic hydrocarbon waxes include low molecular weight polyethylene, low molecular weight polypropylene, polyolefin copolymers, polyolefin waxes, microcrystalline waxes, paraffin waxes, and Fischer-Tropsch waxes. Examples of the oxides of aliphatic hydrocarbon waxes include oxidized polyethylene waxes and block copolymers of oxidized polyethylene waxes. Examples of the vegetable waxes include candelilla wax, carnauba wax, Japan wax, jojoba wax, and rice wax. Examples of the animal waxes include beeswax, lanolin, and spermaceti. Examples of the mineral waxes include ozokerite, ceresin, and petrolatum. Examples of the ester waxes mainly composed of fatty acid esters include montan acid ester wax and castor wax. An example of the wax in which the fatty acid esters are partially or completely deoxidized is deoxidized carnauba wax. As the release agent, carnauba wax is preferred.
[0071] When the toner base particles contain a release agent, a compatibilizer may be added to the toner base particles in order to improve the compatibility between the binder resin and the release agent.
[0072] (Charge control agent) The toner base particles may contain a charge control agent. The charge control agent is used, for example, for the purpose of providing a toner having excellent charge stability or excellent charge rise characteristics. The charge rise characteristics of a toner are an index of whether or not the toner can be charged to a predetermined charge level in a short period of time. By incorporating a positively chargeable charge control agent in the toner base particles, the cationic nature of the toner base particles can be enhanced.
[0073] Examples of the positively charged charge control agent include azine compounds, direct dyes, acid dyes, alkoxylated amines, alkylamides, quaternary ammonium salts, and resins containing quaternary ammonium cationic groups. The charge control agent is preferably a quaternary ammonium salt or a resin containing a quaternary ammonium cationic group.
[0074] From the viewpoint of obtaining a toner having excellent charge stability, the content of the charge control agent is preferably 0.1 parts by mass to 30 parts by mass, more preferably 3 parts by mass to 10 parts by mass, per 100 parts by mass of the binder resin.
[0075] [Toner manufacturing method] The toner can be produced, for example, by a production method including a step of preparing toner base particles and a step of adding an external ingredient.
[0076] (Toner Base Particle Preparation Process) In the toner base particle preparation step, the toner base particles are prepared by, for example, an aggregation method or a pulverization method.
[0077] The aggregation method includes, for example, an aggregation step and a coalescence step. In the aggregation step, fine particles containing components constituting the toner base particles are aggregated in an aqueous medium to form aggregated particles. In the coalescence step, components contained in the aggregated particles are coalesced in the aqueous medium to form the toner base particles.
[0078] Next, the pulverization method will be described. The pulverization method allows the toner base particles to be prepared relatively easily and also allows the production cost to be reduced. When the toner base particles are prepared by the pulverization method, the preparation process of the toner base particles includes, for example, a melt-kneading process and a pulverization process. The preparation process of the toner base particles may further include a mixing process before the melt-kneading process. In addition, the preparation process of the toner base particles may further include at least one of a fine pulverization process and a classification process after the pulverization process.
[0079] In the mixing step, the binder resin and the internal additives added as necessary are mixed to obtain a mixture. In the melting and kneading step, the toner materials are melted and kneaded to obtain a molten and kneaded product. For example, the mixture obtained in the mixing step is used as the toner material. In the pulverizing step, the obtained molten and kneaded product is cooled, for example, to room temperature (25°C), and then pulverized to obtain a pulverized product. If it is necessary to reduce the diameter of the pulverized product obtained in the pulverizing step, a step of further pulverizing the pulverized product (fine pulverizing step) may be performed. In addition, if the particle size of the pulverized product is to be uniform, a step of classifying the obtained pulverized product (classifying step) may be performed. Through the above steps, the pulverized product, that is, toner base particles, is obtained.
[0080] (External addition process) In this process, the toner particles are obtained by adhering the first external additive particles and the external additive including the fluororesin particles to the surface of the toner base particles. The method for adhering the external additive to the surface of the toner base particles is not particularly limited, but may be, for example, a method of stirring the toner base particles and the external additive with a mixer or the like. EXAMPLES
[0081] The present invention will be described in more detail below using examples, but the present invention is not limited to the scope of the examples.
[0082] (Measurement of number average primary particle size) The number-average primary particle diameter of the external additive particles was measured by the following method. First, a transmission electron microscope (TEM) (Hitachi High-Technologies Corporation, "H-7100FA") was used to observe the external additive particles to be measured at a magnification of 1,000,000 times, and TEM photographs of 100 or more external additive particles were taken. From the obtained TEM photographs, TEM photographs of 100 external additive particles were arbitrarily selected. For the arbitrarily selected TEM photographs, the circle equivalent diameter was measured using image analysis software (Mitani Shoji Co., Ltd., "WinROOF"). The number average value of the measured circle equivalent diameters was calculated. The calculated number average value was taken as the number average primary particle diameter of the external additive particles.
[0083] (Measurement of powder resistivity) 5 g of the measurement object (first external additive particles) was put into a cylindrical measurement cell of an electrical resistance meter ("R6561" manufactured by Advantest Corporation). The bottom of the measurement cell was a metal electrode, and the cylindrical part was made of fluororesin. Then, the electrode (superscript: 2, length 25.4 mm) of the electrical resistance meter was connected to the measurement object filled in the measurement cell. A load of 1 kg was applied to this electrode. Then, a DC voltage of 10 V was applied between both electrodes, and the electrical resistance of the measurement object was measured 1 minute after the start of application. A load of 1 kg was continuously applied to the electrode from the start of application to the end of measurement. The measurement was performed in an environment with a temperature of 25°C and a humidity of 50% RH. Then, based on the measured electrical resistance value and the dimensions of the measurement object (specifically, the measurement object filled in the measurement cell) at the time of electrical resistance measurement, the powder resistivity (volume resistivity) of the measurement object was calculated based on the following formula. Powder resistivity [Ω cm] = Electrical resistance value × Cross-sectional area of current path / Length of current path
[0084] (Measurement of desorbed Sn intensity) 5 g of the measurement target (first external additive particles) and 25 g of ethanol were put into a glass bottle, and the bottle was shaken by hand until no precipitate was found, to obtain a mixture. Next, the mixture was subjected to ultrasonic treatment for 1 minute using a tabletop ultrasonic disperser ("US-2KS" manufactured by SND Co., Ltd., output: 100 W, oscillation frequency: 28 kHz). Next, 10 g of ethanol was further added to the mixture, and the mixture was shaken by hand until no precipitate was found. Next, the mixture was subjected to ultrasonic treatment for 5 minutes using an ultrasonic disperser ("Mini Welder UPW0128A1H" manufactured by Ultrasonic Industries Co., Ltd., output: 100 W, oscillation frequency: 28 kHz). Next, the mixture was transferred to a centrifuge tube, and centrifuged at 8000 rpm for 1 minute. Next, the supernatant was collected from the mixture after centrifugation. 1000μL of the above-mentioned supernatant was added to a container for trace powder for X-ray measurement (Rigaku Corporation "3399O053", outer diameter 20mm), and the supernatant was dried. Using the container for trace powder to which the supernatant had been added, X-ray fluorescence analysis was performed under the following conditions. This allowed the measurement of the intensity of Sn desorbed into ethanol when stress (ultrasonic treatment) was applied to the measurement object.
[0085] (X-ray fluorescence analysis) -Analysis equipment: Scanning X-ray fluorescence analyzer (Rigaku Corporation "ZSX") X-ray tube (X-ray source): Rh (rhodium) Excitation conditions: Tube voltage 50 kV, tube current 50 mA Measurement area (X-ray irradiation range): diameter 30 mm ·Measurement element: Sn
[0086] <Toner Preparation> The toners of Examples 1 to 19 and Comparative Examples 1 to 12 were prepared by the following method. In the following description, the "pulverizer" refers to the "Jet Mill (registered trademark) I-2 type" manufactured by Japan Pneumatic Mfg. Co., Ltd. In this pulverizer, a ceramic flat plate was used as the collision plate. The "agitator" refers to a device in which an agitator blade ("AS ONE Agitator Blade R-1345 type" sold by AS ONE Corporation) is attached to a motor ("AS ONE Tornado Motor 1-5472-04" sold by AS ONE Corporation).
[0087] [Preparation of fluorine-containing particles] First, fluorine-containing particles (F-1) to (F-6) were prepared. Details of the fluorine-containing particles (F-1) to (F-6) are shown in Table 1 below.
[0088] (Preparation of fluorine-containing particles (F-1)) An autoclave equipped with a stainless steel anchor-type stirring blade and a temperature-controlling jacket was used as a reaction vessel. Deionized water (3.5 L), ammonium perfluorooctanoate (5 g), and paraffin wax (35 g of "Paraffin Wax-115" manufactured by Nippon Seiro Co., Ltd.) were charged into the reaction vessel. After replacing the atmosphere in the reaction vessel with nitrogen gas and tetrafluoroethylene (TFE), TFE was further pressurized into the reaction vessel, and the reaction vessel was heated so that the temperature of the contents of the reaction vessel reached 45° C. while stirring the contents of the reaction vessel at a stirring speed of 250 rpm, and this temperature was maintained. While pressurizing an aqueous solution of ammonium persulfate (concentration: 1.6% by mass) and an aqueous solution of disuccinic acid peroxide (concentration: 2.4% by mass), TFE was continuously supplied so that the pressure in the reaction vessel was constant (0.75 MPa). Thus, a polymerization reaction was carried out for 60 minutes. 60 minutes after the start of polymerization, the supply of TFE and the stirring of the contents of the reaction vessel were stopped, and the polymerization reaction was terminated. An aqueous solution of ammonium hydroperfluorononanoate (concentration: 10% by mass) (200 g) was added to the latex-like reaction product obtained by the polymerization reaction. Next, warm water was added to the reaction product and the temperature was adjusted to 50°C. Next, nitric acid (concentration: 60% by mass) (20 mL) was added to the reaction product, and the reaction product was stirred at a stirring speed of 600 rpm. As a result, fluororesin particles began to coagulate from the reaction product. Next, the reaction product was stirred for 1.5 hours (stirring time X) to sufficiently separate the fluororesin particles and the solvent. Next, the solvent was removed from the fluororesin particles, and the particles were dried. The obtained fluororesin particles (polytetrafluoroethylene particles, number average primary particle diameter 98 nm) were used as fluorine-containing particles (F-1).
[0089] (Preparation of Fluorine-Containing Particles (F-2) to (F-3)) Fluorine-containing particles (F-2) to (F-3) were prepared in the same manner as in the preparation of fluorine-containing particles (F-1), except that the stirring time X was changed as shown in Table 1 below.
[0090] (Preparation of fluorine-containing particles (F-4)) Perfluoroalkoxy fluororesin particles ("PFA-945HP PLUS" manufactured by Mitsui-Chemours Fluoroproducts, Inc.) were prepared and used as fluorine-containing particles (F-4).
[0091] (Preparation of fluorine-containing particles (F-5)) After adding 100 mL of toluene to the reaction vessel, a fluorine-containing silane coupling agent (CF 3 (CH 2 ) 2 Si(OCH 3 ) 3 ) was further added, and the fluorine-containing silane coupling agent was dissolved in toluene. Next, 100 g of silica particles ("Quartlon (registered trademark) PL-10H" manufactured by Fuso Chemical Co., Ltd., number average primary particle diameter 90 nm) was further added to the reaction vessel. Next, the contents of the reaction vessel were thoroughly stirred and then heated at 130°C for 120 minutes. Next, the contents of the reaction vessel were crushed with a pin mill ("Sample Mill SAM-0 type" manufactured by Nara Machinery Manufacturing Co., Ltd.). This resulted in the production of fluorine-containing particles (F-5) (number average primary particle diameter 98 nm). The fluorine-containing particles (F-5) contained silica particles and a fluorine component layer containing a component derived from the fluorine-containing silane coupling agent.
[0092] (Preparation of fluorine-containing particles (F-6)) 100 g of silica particles ("Quartlon (registered trademark) PL-10H" manufactured by Fuso Chemical Co., Ltd., number average primary particle diameter 90 nm) was put into a stainless steel reaction vessel. After the reaction vessel was filled with nitrogen, 15 g of fluorine-modified silicone oil ("FL-100" manufactured by Shin-Etsu Chemical Co., Ltd.) and 10 mL of n-hexane were sprayed into the reaction vessel while stirring the contents of the reaction vessel at room temperature. After the spraying was completed, the contents of the reaction vessel were further stirred at room temperature for 30 minutes while maintaining the nitrogen atmosphere. Next, the contents of the reaction vessel were stirred at 100°C for 50 minutes, and then further stirred at 200°C for 1.5 hours. Next, the contents of the reaction vessel were allowed to cool to obtain fluorine-containing particles (F-6) (number average primary particle diameter 98 nm). The fluorine-containing particles (F-6) contained silica particles and a fluorine component layer containing fluorine-modified silicone oil.
[0093] [Table 1]
[0094] [Preparation of first external additive particles] The first external additive particles (A) to (T) were prepared by the following method. First, the formation treatment of each protective layer performed in the preparation will be described. In the following, the particles subjected to the formation treatment of each protective layer will be referred to as "particles to be treated".
[0095] (Protection layer (TTS) formation process) 300 g of the particles to be treated and the amount of titanate coupling agent (Ajinomoto Co., Inc.'s "Plenact (registered trademark) TTS", isopropyl triisostearoyl titanate) shown in "Amount A" in Table 2 below were put into a mixer (Kawata Co., Ltd.'s "Nano Version Piccolo") and mixed at 80°C, 1 hour, and 6000 rpm. The mixture obtained was then dried at 110°C for 12 hours. The dried mixture was then pulverized using a pulverizer at a pulverization pressure of 0.6 MPa. This resulted in the production of particles to be treated that were coated with a protective layer containing a component derived from the titanate coupling agent.
[0096] (Protective layer (MM) formation process) A dispersion was prepared by stirring 1.5 L of ion-exchanged water and 300 g of particles to be treated at room temperature for 30 minutes at 30 rpm using a mixer (TK Hivis Dispermix HM-3D-5 manufactured by Primix Corporation). Methylolmelamine (Nikaresin (registered trademark) S-260 manufactured by Nippon Carbide Industries Co., Ltd.) in an amount shown in "Amount A" in Table 2 below was added to the obtained dispersion, and the mixture was stirred at room temperature for 5 minutes at 30 rpm. After mixing, the contents of the mixer were transferred to a separable flask equipped with a thermometer and a stirring blade. The contents of the separable flask were heated from 35°C to 70°C at a rate of 5°C / 15 minutes while being stirred at 200 rpm using a stirring device. Next, the contents of the separable flask were stirred at a rotation speed of 90 rpm for 30 minutes while maintaining the temperature at 70°C. As a result, a protective layer was formed on the surface of the particles to be treated. The contents of the separable flask were then cooled to room temperature and filtered using a Buchner funnel. The wet cake-like residue was dispersed in an aqueous ethanol solution (50% by mass of ethanol) to prepare a slurry. The resulting slurry was fed to a continuous surface modification device ("Coatmizer (registered trademark)" manufactured by Freund Corporation) and dried to obtain a coarse powder. The drying conditions using the continuous surface modification device were a hot air temperature of 45°C and a blower air volume of 2 m. 3 The obtained coarse powder was pulverized at a pulverization pressure of 0.6 MPa using a pulverizer, thereby obtaining target particles coated with a protective layer containing a methylol melamine resin.
[0097] (Protective layer (sUR) formation process) A dispersion was prepared by stirring 1.5 L of ion-exchanged water and 300 g of particles to be treated at room temperature for 30 minutes at 30 rpm using a mixer (TK Hivis Dispermix HM-3D-5 manufactured by Primix Corporation). A water-soluble urethane resin (Superflex (registered trademark) 170 manufactured by Daiichi Kogyo Seiyaku Co., Ltd., an aqueous solution with a solid content concentration of 30% by mass) in an amount shown in "Amount A" in Table 2 below was added to the obtained dispersion, and the mixture was stirred at room temperature for 5 minutes at 30 rpm. After mixing, the contents of the mixer were transferred to a separable flask equipped with a thermometer and a stirring blade. The contents of the separable flask were heated from 35°C to 70°C at a rate of 5°C / 15 minutes while stirring at 200 rpm using a stirring device. Next, the contents of the separable flask were stirred at a rotation speed of 90 rpm for 30 minutes while maintaining the temperature at 70°C. The contents of the separable flask were then cooled to room temperature and filtered using a Buchner funnel. The wet cake-like residue was dispersed in an aqueous ethanol solution (50% by mass of ethanol) to prepare a slurry. The resulting slurry was fed to a continuous surface modification device ("Coatmizer (registered trademark)" manufactured by Freund Corporation) and dried to obtain a coarse powder. The drying conditions using the continuous surface modification device were a hot air temperature of 45°C and a blower air volume of 2 m. 3 The obtained coarse powder was pulverized at a pulverization pressure of 0.6 MPa using a pulverizer, thereby obtaining target particles coated with a protective layer containing a urethane resin.
[0098] (Protective layer (pAl) formation process) A dispersion was prepared by stirring 1.5 L of ion-exchanged water and 300 g of particles to be treated at room temperature for 30 minutes at 30 rpm using a mixer (TK Hivis Dispermix HM-3D-5 manufactured by Primix Corporation). The obtained dispersion was heated to 45°C, and then an aqueous polyaluminum chloride solution (manufactured by Takasugi Pharmaceutical Co., Ltd., concentration 61.3 g / L) and a 5N aqueous sodium hydroxide solution were simultaneously dropped. The amount of the aqueous polyaluminum chloride solution was adjusted so that the active ingredient (polyaluminum chloride) was the amount shown in "Amount A" in Table 2 below. During the dropping, the dispersion was kept at 45°C and the amount dropped was adjusted so that the pH of the dispersion was kept at 6.0. The dispersion after the dropping was cooled to 30°C and then filtered using a Buchner funnel. The obtained wet cake-like filtrate was dispersed in an aqueous ethanol solution (50% by mass of ethanol) to prepare a slurry. The obtained slurry was supplied to a continuous surface modification device ("Coatmizer (registered trademark)" manufactured by Freund Corporation) and dried to obtain a coarse powder. The drying conditions using the continuous surface modification device were hot air temperature of 45°C and blower volume of 2 m 3 The obtained coarse powder was pulverized at a pulverization pressure of 0.6 MPa using a pulverizer, thereby obtaining target particles coated with a protective layer containing aluminum hydroxide.
[0099] (Protective layer (iBTMS) formation process) 300 g of the particles to be treated were mixed with the amount of a silane coupling agent (Tokyo Chemical Industry Co., Ltd.'s "isobutyltriethoxysilane") shown in "Amount A" in Table 2 below, and 50 g of an aqueous ethanol solution (ethanol 90% by mass). The resulting mixture was placed in a mixer (Kawata Co., Ltd.'s "Nano Version Piccolo") and mixed at 80°C for 1 hour at 6000 rpm. The resulting mixture was then dried at 110°C for 12 hours. The dried mixture was then pulverized using a pulverizer at a pulverization pressure of 0.6 MPa. As a result, the particles to be treated were obtained that were coated with a protective layer containing a component derived from the silane coupling agent.
[0100] (Protective layer (SiO) formation process) 1.5L of n-hexane ("n-hexane first grade" manufactured by Wako Pure Chemical Industries, Ltd.) and methyl hydrogen silicone oil ("KF-99" manufactured by Shin-Etsu Chemical Co., Ltd.) in an amount shown in "Amount A" in Table 2 below were added to a mixer ("TK Hivis Dispermix HM-3D-5 type" manufactured by Primix Corporation) to dissolve the methyl hydrogen silicone oil in n-hexane. Next, 300g of the particles to be treated was added to the n-hexane solution in the mixer. After that, the contents of the mixer were stirred at room temperature for 30 minutes at 30 rpm. After stirring, the contents of the mixer were transferred to a separable flask equipped with a thermometer and a stirring blade. The contents of the separable flask were heated from 35°C to 70°C at a rate of 5°C / 15 minutes while being stirred at 200 rpm using a stirring device. Then, the contents of the separable flask were dried in a vacuum dryer while maintaining the temperature of the contents of the separable flask at 70°C (vacuum drying process). The vacuum drying process was continued until the contents of the flask were completely dried and the mass was constant. The contents after the vacuum drying process were placed in an electric furnace and baked at 200°C for 3 hours in a nitrogen atmosphere. The coarse powder obtained by baking was pulverized using a pulverizer at a crushing pressure of 0.6 MPa. This resulted in the preparation of treated particles coated with a protective layer containing silicone oil.
[0101] (Preparation of First External Additive Particles (A)) (Preparation of Aluminum Oxide Particles) A high-speed rotary shear agitator ("Clearmix (registered trademark) CLM-2.2S" manufactured by M-Technique Co., Ltd., rotor used had a maximum diameter of 57 mm, a minimum diameter of 25 mm, and a clearance of 0.3 mm) was installed in a pressure-resistant vessel, which served as a reaction vessel. A mixed solution A of aluminum isopropoxide and isopropyl alcohol (aluminum isopropoxide concentration: 60 mass%) and a mixed solution B of water and isopropyl alcohol (water concentration: 30 mass%) were prepared in the reaction vessel. The contents of the reaction vessel were stirred at 70°C while continuously feeding mixed solutions A and B into the reaction vessel. The amounts of mixed solutions A and B fed were such that the molar ratio of water to aluminum isopropoxide (water / aluminum isopropoxide) was 2.5. In the stirring, the velocity gradient was set to 100,000 / sec, and the residence time in the stirring zone was set to the time shown in "Stirring time B" in Table 2 below. As a result, a hydrolysis reaction occurred in the contents of the reaction vessel, and aluminum hydroxide was obtained. The aluminum hydroxide thus obtained was calcined at 800° C. for 3 hours to obtain aluminum oxide, which was then pulverized at a pulverization pressure of 0.9 MPa using a pulverizer to obtain aluminum oxide particles having a number-average primary particle size of 200 nm.
[0102] (Conductive layer formation process) 300 g of the obtained aluminum oxide particles were dispersed in pure water using a "Homomixer MARK II 2.5" manufactured by Primix Corporation to prepare 2 L of suspension. The obtained suspension was heated to 70 °C and maintained at this temperature. In 750 mL of 2.4 N hydrochloric acid prepared separately, stannic chloride pentahydrate (SnCl ) in the amount shown in "Amount C" in Table 2 below was added. 4 5H 2 O) and the amount of antimony trichloride (SbCl 3) was dissolved to prepare an acid solution. A 5N aqueous ammonia solution and the above-mentioned acid solution were dropped in parallel to the above-mentioned suspension over 1.5 hours. In the parallel dropping, the suspension was kept at 70°C, and the drop amount was adjusted so that the pH of the suspension was kept at 7 to 8. The suspension was then filtered. Pure water was added to the obtained filtrate, and the suspension was filtered again (washing treatment). The washing treatment was repeated until the conductivity of the filtrate became 50 μS / cm or less. The washed filtrate was dried at 110°C for 15 hours, and then fired in an electric furnace at 700°C for 2 hours. The obtained fired product was pulverized using a pulverizer at a pulverization pressure of 0.8 MPa. As a result, first particles having aluminum oxide particles and a conductive layer containing ATO were obtained.
[0103] (Protective Layer Formation Treatment) The first particles were subjected to the above-mentioned protective layer (TTS) forming treatment. As a result, the first external additive particles (A) (number average primary particle diameter 204 nm) having aluminum oxide particles, a conductive layer containing ATO, and a protective layer were obtained. The protective layer had a single layer structure including a layer containing a component derived from a titanate coupling agent.
[0104] (Preparation of First External Additive Particles (T)) A mixture of titanium tetrachloride obtained by the chlorine method and oxygen gas was introduced into a gas phase oxidation reactor and reacted in the gas phase at a temperature of 1000°C for 3 hours to obtain bulk titanium oxide. This bulk titanium oxide was pulverized with a hammer mill, and the pulverized material obtained was washed and then dried at 110°C. The dried pulverized material was disintegrated (pressure 1.0 MPa) using a supersonic jet pulverizer ("Jet Mill IDS-2" manufactured by Nippon Pneumatic Mfg. Co., Ltd.) to obtain titanium oxide particles (number average primary particle diameter: 204 nm, crystal type: rutile type). The number average primary particle diameter of the titanium oxide particles was adjusted by the settings of the hammer mill.
[0105] Except for using 300 g of titanium oxide particles instead of 300 g of aluminum oxide particles, a conductive layer was formed on the titanium oxide particles in the same manner as the conductive layer formed on the first external additive particles (A). This resulted in first particles having titanium oxide particles and a conductive layer containing ATO. Next, the above-mentioned protective layer (TTS) was formed on the first particles. This resulted in first external additive particles (T) having titanium oxide particles, a conductive layer containing ATO, and a protective layer. The protective layer had a single layer structure including a layer containing a component derived from a titanate coupling agent.
[0106] (Preparation of First External Additive Particles (B) to (S)) The mixing time B in the preparation of aluminum oxide particles and the amount of stannic chloride pentahydrate (SnCl 4 5H 2 O) and antimony trichloride (SbCl 3 The first external additive particles (B) to (S) were prepared in the same manner as the preparation of the first external additive particles (A), except that the amount D of the first external additive particles (A) and the protective layer formation treatment were changed as shown in Table 2 below.
[0107] In Table 2 below, "diameter" refers to the number-average primary particle diameter. "Al" and "Ti" in the substrate refer to aluminum oxide particles and titanium oxide particles. "TTS", "iBTMS", "MM", "sUR", "pAl" and "SiO" in the protective layer respectively indicate that the above-mentioned "treatment for forming protective layer (TTS)", "treatment for forming protective layer (iBTMS)", "treatment for forming protective layer (MM)", "treatment for forming protective layer (sUR)", "treatment for forming protective layer (pAl)" and "treatment for forming protective layer (SiO)" were carried out.
[0108] For example, in Table 2 below, the first external additive particles (D) indicate that the aluminum oxide particles were subjected to a conductive layer formation treatment, followed by a protective layer (TTS) formation treatment and a protective layer (iBTMS) formation treatment in that order. Also, the first external additive particles (P) indicate that the aluminum oxide particles were subjected to a protective layer (TTS) formation treatment without a conductive layer formation treatment.
[0109] [Table 2]
[0110] [Preparation of toner base particles] 87.0 parts by mass of polyester resin ("Polyester (registered trademark) HP-313" manufactured by Nippon Synthetic Chemical Industry Co., Ltd.), 3.0 parts by mass of carbon black ("MA100" manufactured by Mitsubishi Chemical Corporation), 4.0 parts by mass of carnauba wax (manufactured by Toa Kasei Co., Ltd.), 2.0 parts by mass of an azine compound ("BONTRON (registered trademark) N-71" manufactured by Orient Chemical Industries Co., Ltd.) as a charge control agent, and 4.0 parts by mass of a polymer type positively charged charge control agent ("ACRYBASE (registered trademark) FCA-201-PS" manufactured by Fujikura Kasei Co., Ltd.) were mixed using an FM mixer ("FM-10B" manufactured by Nippon Coke and Engineering Co., Ltd.).
[0111] The resulting mixture was kneaded while melting using a twin-screw extruder ("TEM-26SS" manufactured by Toshiba Machine Co., Ltd.) to obtain a kneaded product. The kneaded product was coarsely pulverized using a pulverizer ("Rotoplex (registered trademark) 16 / 8 type" manufactured by the former Toa Machinery Works, Ltd.) until the kneaded product had a size of about 2 mm to obtain a coarsely pulverized product. The coarsely pulverized product was further pulverized using a pulverizer ("Turbo Mill RS type" manufactured by Freund Turbo Corporation) to obtain a finely pulverized product. The finely pulverized product was classified using a classifier ("Elbow Jet EJ-LABO type" manufactured by Nittetsu Mining Co., Ltd.). As a result, toner base particles were obtained. The D of the toner base particles 50 was 8.0 μm.
[0112] [External Addition Treatment] Using an FM mixer ("FM-10B" manufactured by Nippon Coke & Engineering Co., Ltd.), 100.0 parts by mass of toner base particles, 1.5 parts by mass of silica particles (fumed silica particles with hydrophobic surface treatment, "CAB-O-SIL (registered trademark) TG-308F" manufactured by Cabot Corporation), and the types and amounts of external additive particles (specifically, any of the fluorine-containing particles (F-1) to (F-6) and any of the first external additive particles (A) to (T)) shown in Table 3 below were mixed at 3500 rpm for 5 minutes. As a result, the external additive was attached to the surface of the toner base particles, and the toners of Examples 1 to 19 and Comparative Examples 1 to 12 were obtained.
[0113] The first external additive particles were measured for the desorbed Sn strength and powder resistivity of the toners of Examples 1 to 19 and Comparative Examples 1 to 12. The measurement results are shown in Table 3 below.
[0114] [Table 3]
[0115] <Evaluation> The toners of Examples 1 to 19 and Comparative Examples 1 to 12 were evaluated by the following methods for the occurrence or absence of fogging, charge amount, and filming resistance in a high-temperature, high-humidity environment (HH environment) at a temperature of 32.5°C and a humidity of 80% RH, and the charge amount, toner transport amount, image density stability, and toner recovery in a low-temperature, low-humidity environment (LL environment) at a temperature of 10.0°C and a humidity of 10% RH. The results are shown in Tables 4 to 6 below. Each evaluation was performed after leaving the toner in each environment (HH environment or LL environment) for 24 hours using the following evaluation machine.
[0116] [Evaluation machine] A non-magnetic one-component image forming apparatus (modified version of "HL-1040" manufactured by Brother Industries, Ltd.) was used as the evaluation machine. The evaluation target (any of the toners of Examples 1 to 19 and Comparative Examples 1 to 12) was placed in the developing device of the evaluation machine. A4-sized plain paper ("ColorCopy (registered trademark)" manufactured by Mondi) was used as the recording medium.
[0117] [Fogging in HH environment] Under an HH environment, one pattern image (printing rate 5%) was formed on a recording medium using an evaluation machine. Using a reflection densitometer (X-Rite Corp. "RD918"), the image density of the blank portion of the recording medium on which the pattern image was formed was measured. Separately, the image density of an unused recording medium was measured. The fog density (FD) was calculated based on the following formula. The obtained fog density was used as the evaluation value of fog. Fog was evaluated according to the following criteria. FD = (image density of blank area) - (image density of unused recording medium)
[0118] (Standard for fogging in HH environment) A (Good): Fog density is 0.010 or less B (bad): Fog density exceeds 0.010
[0119] [Amount of static electricity in a HH environment] After the evaluation of fogging in the HH environment, the developing device was removed from the evaluation machine. Using a Q / m meter (Trek Model 210HS-1), the toner was sucked from the toner layer in the area immediately before the development nip on the developing sleeve of the developing device, and the charge amount [μC / g] was measured. The charge amount was evaluated according to the following criteria.
[0120] (Standard for charge amount in HH environment) A (Good): Charge amount is 10μC / g or more and 30μC / g or less B (bad): Charge amount is less than 10 μC / g or more than 30 μC / g
[0121] [Filming resistance in HH environment] Under the HH environment, 2000 pattern images (printing rate 5%) were formed on a recording medium using the evaluation machine. Next, the photoconductor drum was removed from the evaluation machine, and the surface of the photoconductor drum was observed with a digital microscope ("VHX-6000" manufactured by Keyence Corporation). In the observation, the presence or absence of toner-derived adherent matter on the surface of the photoconductor drum was confirmed. The filming resistance was evaluated according to the following criteria.
[0122] (Standard for filming resistance under HH environment) A (Good): No adhesions observed B (bad): Adhesion observed
[0123] [Amount of static electricity in LL environment] Under LL environment, one pattern image (printing rate 5%) was formed on a recording medium using the evaluation machine. Next, the developing device was removed from the evaluation machine. Using the above-mentioned Q / m meter, toner was sucked from the toner layer in the area immediately before the development nip portion on the developing sleeve of the developing device, and its charge amount [μC / g] was measured. The obtained value was taken as the initial charge amount.
[0124] Next, 2000 pattern images (printing rate 5%) were formed on the recording medium using the evaluation machine. Using the above-mentioned Q / m meter, toner was sucked from the toner layer in the area immediately before the development nip portion of the development sleeve of the development device, and its charge amount [μC / g] was measured. The obtained value was taken as the charge amount after printing. The initial charge amount and the charge amount after printing were evaluated according to the following criteria.
[0125] (Standard for charge amount in LL environment) A (Good): Charge amount is 10μC / g or more and 30μC / g or less B (bad): Charge amount is less than 10 μC / g or more than 30 μC / g
[0126] [Toner transport volume in LL environment] In the measurement of the "initial charge amount under LL environment" mentioned above, the mass of the toner that was attracted [g] and the surface area [m2] of the developing sleeve onto which the toner was attracted were measured using a Q / m meter. 2 Specifically, the initial toner transport amount [g / m2] was calculated from the formula "toner transport amount = mass of sucked toner / surface area of the developing sleeve where the toner was sucked". 2 Similarly, the toner transport amount after printing was calculated based on the measurement of the "charge amount after printing under LL environment" described above. The initial toner transport amount and the toner transport amount after printing were evaluated according to the following criteria.
[0127] (Standard toner transport volume in LL environment) A (Good): Toner transport amount is 3.5 g / m 2 More than 7.5g / m 2 below B (bad): Toner transport amount is 3.5 g / m 2 Less than 7.5g / m 2 Super
[0128] [Image density stability under LL environment] Under LL environment, 2000 solid images were formed on a recording medium using the evaluation machine. Using the reflection densitometer described above, the image density of the solid image formed on the first sheet (initial image density) and the image density of the solid image formed on the 2000th sheet (image density after printing) were measured. The absolute value (ΔID) of the difference between the initial image density and the image density after printing was calculated. The initial image density, the image density after printing, and ΔID were evaluated according to the following criteria.
[0129] (Standards for initial image density and image density after printing) A (good): 1.3 or more and 1.5 or less B (fairly good): 1.2 or more and less than 1.3 C (poor): Less than 1.2 or more than 1.5
[0130] (ΔID standard) A (good): 0.1 or less B (slightly good): Over 0.1 and below 0.2 C (bad): over 0.2
[0131] [Toner recovery] In the evaluation of toner recovery, an evaluation image shown in FIG. 6, which will be described below, was formed. The evaluation image I shown in FIG. 6 is formed by two rotations of the photosensitive drum of the evaluation machine. For convenience, in the evaluation image I, the area formed in the first rotation of the photosensitive drum is called the first area X, and the area formed in the second rotation of the photosensitive drum is called the second area Y. The first area X includes a solid image S located in the widthwise center and a first non-printed portion B1 located at both ends in the widthwise direction. The widths of the solid image S and the first non-printed portion B1 are the same. The second area Y includes a second non-printed portion B2 located in the widthwise center and a third non-printed portion B3 located at both ends in the widthwise direction. The solid image S and the second non-printed portion B2 are formed by the same area on the surface of the photosensitive drum. In other words, in the area near the widthwise center of the photosensitive drum, the first area X is formed in the first rotation of the photosensitive drum, and then the second non-printed portion B2 is formed in the second rotation of the photosensitive drum. Similarly, the first non-printed portion B1 and the third non-printed portion B3 are formed in the same region on the surface of the photosensitive drum. That is, in the regions near both ends of the width direction of the photosensitive drum, the first non-printed portion B1 is formed during the first rotation of the photosensitive drum, and then the third non-printed portion B3 is formed during the second rotation of the photosensitive drum.
[0132] In an image forming apparatus, when the amount of toner transported is excessive, fogging may occur due to poor recovery of the toner developed on the photosensitive drum. In more detail, when the amount of toner transported is excessive in an image forming apparatus, the toner is excessively developed on the electrostatic latent image on the photosensitive drum. The toner excessively developed on the photosensitive drum is not all transferred to the recording medium on the first rotation of the photosensitive drum, and a part of it remains on the photosensitive drum as residual toner. When the amount of residual toner remaining on the photosensitive drum is large, the residual toner is not completely recovered even by the cleaning member of the image forming apparatus, and the residual toner is transferred to the recording medium on the second rotation of the photosensitive drum. This causes fogging due to the residual toner.
[0133] In the evaluation of toner collectability, the toner collectability was evaluated based on the occurrence of fogging caused by residual toner. More specifically, when fogging caused by residual toner occurs, fogging caused by the residual toner during the formation of the solid image S occurs in the second non-printed portion B2. Therefore, the fogging density in the second non-printed portion B2 was measured. Specifically, the above-mentioned reflection densitometer was used to measure the image density in the second non-printed portion B2 and the image density of an unused recording medium. Then, the fogging density (FD A In order to eliminate the influence of fogging caused by factors other than the residual toner, the fogging density (FD B ) was also measured. Specifically, the image density in the third non-printed portion B3 and the image density of an unused recording medium were measured using the above-mentioned reflection densitometer. Next, the fog density (FD B ) was calculated based on the following formula (3). A ) to the fog density caused by substances other than residual toner (FD B The influence of the above factors was eliminated, and the obtained value was used as the evaluation value of the toner recovery property. FD A = (image density of second non-printed portion B2) - (image density of unused recording medium) (1) FD B = (image density of the third non-printed portion B3) - (image density of an unused recording medium) (2) Evaluation value = FD A -FD B (3)
[0134] [Table 4]
[0135] [Table 5]
[0136] [Table 6]
[0137] The toners of Examples 1 to 19 each contained toner particles. The toner particles included toner base particles and an external additive attached to the surface of the toner base particles. The external additive included first external additive particles and fluorine-containing particles. The first external additive particles included aluminum oxide particles, a conductive layer covering the aluminum oxide particles, and a single-layer or multi-layer protective layer covering the conductive layer. The conductive layer contained antimony-doped tin oxide. The protective layer had a layer containing a component derived from a titanate coupling agent, or had an inner layer containing methylol melamine, a urethane resin, or aluminum hydroxide, and an outer layer containing a component derived from a silane coupling agent. The powder resistivity of the first external additive particles was 50 Ω·cm or less. The number-average primary particle diameter of the first external additive particles was 60 nm or more and 600 nm or less. As shown in Tables 4 to 6, the toners of Examples 1 to 19 each had excellent image density stability, charge stability, and filming resistance. Furthermore, the toners of Examples 1 to 19 were also able to suppress the occurrence of fogging caused by residual toner.
[0138] On the other hand, the toners of Comparative Examples 1 to 12 did not have the above-mentioned configuration, and therefore were poor in at least one of image density stability, charge stability, and filming resistance.
[0139] Specifically, the toner of Comparative Example 1 did not contain fluorine-containing particles, and therefore the image density stability was poor.
[0140] The toner of Comparative Example 2, which does not contain the first external additive particles, was poor in image density stability, charge stability, and filming resistance.
[0141] The toners of Comparative Examples 3, 4, 9, 10 and 11 had poor charging stability or image density stability because the first external additive particles did not have a predetermined protective layer.
[0142] The number average primary particle diameter of the first external additive particles was excessively small or excessively large in the toners of Comparative Examples 5 and 6. As a result, the toners of Comparative Examples 5 and 6 were poor in image density stability, charge stability, or filming resistance.
[0143] The toner of Comparative Example 7 had poor charging stability and image density stability because the powder resistivity of the first external additive particles was large.
[0144] The toner of Comparative Example 8 had poor image density stability and charging stability because the first external additive particles did not have a conductive layer.
[0145] The toner of Comparative Example 12 had poor charging stability because the base material of the first external additive particles was titanium oxide particles rather than aluminum oxide particles. [Industrial Applicability]
[0146] The toner of the present invention can be used to form images in, for example, a copier, a printer, or a multifunction machine. [Explanation of symbols]
[0147] 1 Toner particles 2. Toner base particles 3. External additive particles 3a First external additive particles 3b Fluorine-containing particles 3c Silica particles 4. Aluminum oxide particles 5 Conductive layer 6 Multiple layers of protection 6a Inner layer 6b Outer layer 7 Single layer of protection 8 Fluorine resin particles 9 Base 10 Fluorine component layer
Claims
1. A toner comprising toner particles, The toner particles include toner base particles and an external additive attached to the surface of the toner base particles, The external additive includes first external additive particles and fluorine-containing particles, the first external additive particle includes an aluminum oxide particle, a conductive layer covering the aluminum oxide particle, and a single-layer or multi-layer protective layer covering the conductive layer; the conductive layer contains antimony-doped tin oxide; The protective layer is having a layer containing a component derived from a titanate coupling agent, or The adhesive has an inner layer containing methylol melamine, a urethane resin or aluminum hydroxide, and an outer layer containing a component derived from a silane coupling agent, The powder resistivity of the first external additive particles is 50 Ω cm or less, The toner, wherein the first external additive particles have a number average primary particle diameter of 60 nm or more and 600 nm or less.
2. The protective layer is A single layer structure including a layer containing a component derived from a titanate coupling agent; A two-layer structure including an inner layer containing a component derived from a titanate coupling agent and an outer layer containing a component derived from a silane coupling agent or a silicone oil; and 2. The toner according to claim 1, having one of a two-layer structure including an inner layer containing methylol melamine, a urethane resin or aluminum hydroxide, and an outer layer containing a component derived from a silane coupling agent.
3. 3. The toner according to claim 1, wherein the number average primary particle diameter of the fluorine-containing particles is 50 nm or more and 300 nm or less.
4. The fluorine-containing particles include fluorine resin particles or second external additive particles, The second external additive particle includes a substrate and a fluorine component layer that covers the substrate, 4. The toner according to claim 1, wherein the fluorine component layer contains a component derived from a fluorine-containing silane coupling agent or a fluorine-modified silicone oil.
5. The toner according to claim 4 , wherein the fluororesin particles contain polytetrafluoroethylene or perfluoroalkoxy fluororesin.
6. The toner according to claim 4 or 5, wherein the substrate is silica particles.
Citation Information
Patent Citations
Toner for electrophotography
JP1991068957A
White electroconductive powder and its production
JP1997249820A
Nonmagnetic one-component toner
JP2001013712A
Method for manufacturing electrophotographic toner
JP2007047607A
Positive charge type electrophotographic toner
JP2009128778A